2017
DOI: 10.1177/1948550617734616
|View full text |Cite
|
Sign up to set email alerts
|

Faces Tell Everything in a Just and Biologically Determined World: Lay Theories Behind Face Reading

Abstract: The present research investigated an often presumed but rarely assessed construct named the physiognomic belief—a generic belief that various traits can be inferred from faces. Studies in Japan and the United States have demonstrated that this belief can be measured reliably and invariantly across cultures and that those having stronger beliefs make more extreme trait inferences from faces. Of note, in both countries, the physiognomic belief is positively associated with a biologically deterministic view of pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 52 publications
1
27
0
1
Order By: Relevance
“…Finally, autistic traits appear to represent an important individual difference underlying how facial impressions guide trust decisions, a relatively new area of study. In future, it will be important to chart the contributions of other individual differences, such as other key personality traits (Chan & Chen, ) or beliefs around the validity of facial appearance as a guide to trustworthy character (Suzuki, Tsukamoto, & Takahashi, ).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, autistic traits appear to represent an important individual difference underlying how facial impressions guide trust decisions, a relatively new area of study. In future, it will be important to chart the contributions of other individual differences, such as other key personality traits (Chan & Chen, ) or beliefs around the validity of facial appearance as a guide to trustworthy character (Suzuki, Tsukamoto, & Takahashi, ).…”
Section: Discussionmentioning
confidence: 99%
“…1936;Lavater, 1775). For example, Hassin and Trope (2000) report that most people believe that faces contain at least some valid cues to individual personality traits (see also Suzuki, Tsukamoto, & Takahashi, 2017). We refer to this explanation of the face bias as the subjective validity account.…”
Section: Explanations For Reliance On Facial Trustworthinessmentioning
confidence: 99%
“…Inverting photos or misaligning its parts might disrupt the efficient processing of faces while still enabling the identification of an individual 7 An anonymous reviewer raised the possibility that people might simply be reluctant to report that they see faces as valid cues. While more research is needed to measure how accurate people think their face judgments are, the available evidence suggests that people do think and report that faces contain information about a person's personality (Hassin & Trope, 2000;Suzuki et al, 2017). For example, in a survey by Hassin and Trope (2000), they found that 75% of respondents agreed that at least some traits can be read from a person's facial appearance.…”
Section: Implications For Debiasing Interventionsmentioning
confidence: 99%
“…Indeed, although race bias is among the most widely discussed prejudices (Charlesworth & Banaji, 2019), "face bias" appears to be much less of a societal concern. Rather, perceivers appear willing to profess judgment on facial physiognomy and show little correction even when given ample time (Willis & Todorov, 2006) or when explicitly confronted with their inaccuracy (Suzuki, 2018;Suzuki, Tsukamoto, & Takahashi, 2019). Thus, while perceivers may correct for the influence of face-race cues to conform to socially desirable responses, it is less likely that perceivers will correct for the influence of face-trait cues.…”
Section: Relative Importance Of Face-trait Versus Face-race Cuesmentioning
confidence: 99%